Oyster Peptide-Zinc Complex Ameliorates Di-(2-ethylhexyl) Phthalate-Induced Testis Injury in Male Mice and Improving Gut Microbiota - Zhen Lu; Qianqian Huang; Fujia Chen; Enzhong Li; Haisheng Lin; Xiaoming Qin (Foods, 2023)
Di-(2-ethylhexyl) phthalate (DEHP) is a widely used plasticizer, which can cause damage to male reproductive organs, especially the atrophy of the testis. Meanwhile, DEHP can also lead to a decrease in testicular zinc content, but the role of zinc remains unclear. This study aims to prepare oyster peptide-zinc complex (OPZC) to alleviate DEHP-induced reproductive damage in mice. OPZC was successfully obtained through electron microscopy, X-ray diffraction, and thermogravimetric analysis, with stable structure and high water-solubility. Low dose oyster peptide-zinc complex (OPZCL) significantly reduced the reproductive damage caused by DEHP in mice. Further research had shown that OPZCL restored the content of serum hormones and the activity of oxidative stress kinases to normal, while also normalizing testicular zinc and selenium levels. In addition, it also recovered the disorder of gut microbiota, reduced the proportion of Bacteroides, increased the abundance of Ligilactobacillus, and restored the proportion of Acidobacteriota, Chloroflexi, and Proteobacteria. Therefore, OPZCL can relieve the reproductive damage caused by DEHP in mice by restoring testicular zinc homeostasis and the composition of intestinal microbiota, indicating that OPZCL has a potential protective effect on male reproductive health.